Identity and variability of Pythium species associated with yield decline in aerobic rice cultivation in the Philippines - Van Buyten, E.; Banaay, C. G. B.; Vera Cruz, C.; Höfte, M. (Wiley, 2013)
The cultivation of aerobic rice in the tropics enables farmers to save water without lowering productivity. Unfortunately, this system suffers from declining yields due to a disease complex involving nematodes, pathogenic Pythium spp. and nutrient deficiencies. Assessing the impact of each underlying factor can contribute to efficient disease control measures. This study therefore investigated pathogenic and genotypic variability among Pythium species from affected aerobic rice fields in the Philippines using pathogenicity assays and sequence information from the internal transcribed spacer (ITS) region and β‐tubulin gene. Three closely related Pythium spp., P. arrhenomanes, P. graminicola and P. inflatum, were recovered from affected aerobic rice fields. All P. arrhenomanes isolates reduced rice seedling growth, whereas only a few P. graminicola isolates and no P. inflatum isolates were pathogenic, indicating that P. arrhenomanes is probably the most important species affecting rice. Both P. arrhenomanes and P. graminicola isolates showed little genetic variation, despite the observed pathogenic variation within P. graminicola. Intraspecific variation was higher among P. inflatum isolates, but again no correlation was observed with phenotype. When screening P. arrhenomanes isolates from other hosts such as sugarcane, maize and several grasses, a link between pathogenic and genetic variability was detected. However, rice and maize isolates seemed to lack host specificity, and therefore crop rotation with maize might be a risky strategy to manage yield decline in Philippine aerobic rice fields.